2012
DOI: 10.1109/tmm.2012.2196508
|View full text |Cite
|
Sign up to set email alerts
|

Wireless H.264 Video Quality Enhancement Through Optimal Prioritized Packet Fragmentation

Abstract: We introduce a cross-layer priority-aware packet fragmentation scheme at the MAC layer to enhance the quality of pre-encoded H.264/AVC compressed bitstreams over bit-rate limited error-prone links in wireless networks. The H.264 slices are classified in four priorities at the encoder based on their cumulative mean square error (CMSE) contribution towards the received video quality. The slices of a priority class in each frame are aggregated into video packets of corresponding priority. We derive the optimal fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…In this method, division of a frame into slices consequently reduces the overall transmission rate and the effectiveness of video compression is degraded. Slices can be prioritized based on the contribution of distortion to the video quality [6]. Information about slice importance is signaled to the Media Access Control (MAC) layer in order to separate bitstreams into different packets.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, division of a frame into slices consequently reduces the overall transmission rate and the effectiveness of video compression is degraded. Slices can be prioritized based on the contribution of distortion to the video quality [6]. Information about slice importance is signaled to the Media Access Control (MAC) layer in order to separate bitstreams into different packets.…”
Section: Introductionmentioning
confidence: 99%
“…It is imperative from equation (3), that the higher packet loss probability would favor the smaller frame size, but at the expense of additional overhead associated with the number of bytes attached to each header. Another interesting point often neglected in the simulated studies is the fact that the intermediate node's latency sharply increases due to the number of packet processed in a specific time interval [11].…”
Section: The Mac Layer (Enodeb⇔ue) For Lte Network Is Quitementioning
confidence: 99%
“…A somewhat similar study related to work, employing a cross layer approach, is reported in [11], but the results are generated in a simulated environment. The focus of that paper is on prioritizing video slices based on the mean square error rate at VCL layer.…”
Section: Related Workmentioning
confidence: 99%
“…H.264 slices can be prioritized based on their distortion contribution to the received video quality [9,[33][34][35][36][37]. In this paper, the total distortion of a slice loss is computed using the cumulative mean square error (CMSE), which takes into consideration the error propagation within the entire GOP [9,34]. Let the original uncompressed video frame at time t be f (t), the decoded frame without the slice loss bef (t), and the decoded frame with the slice loss bef (t).…”
Section: Priority Assignment For H264 Video Slicesmentioning
confidence: 99%
“…Since computing the video PSNR requires decoding the video at the receiver, it is not feasible to use PSNR directly as the optimization metric due to its heavy computational complexity. The PSNR of a compressed video stream depends on several factors, including the video characteristics, bit rate, the percentage of lost slices, and their CMSE values [9,34]. Therefore, we define a function 'normalized F, ' denoted by F, which represents the weighted distortion contributed by the slice loss rates and their corresponding normalized CMSE values, as…”
Section: Formulation Of Optimization Problemmentioning
confidence: 99%